Charon, Hermes and Alexander: an anonyme Byzantine mime (Circe de clásicos y modernos, 2023)
It is edited, translated, annotated and commentated a text that is included in the manuscript Ambrosianus Graecus 855. It is proposed that this text is a short mime, that it can be performed in limited premises, with satirical intention; and that its authorship may be awarded to Theodorus Prodromos.
Keywords: mime; theatre; Byzantium; Theodorus Prodromos; mythology; Alexander the Great